Corruption, Provincial Institutions and Capital Structure: New Evidence From a Transitional Economy - Thanh, Le Trung (Organizations and Markets in Emerging Economies, 2017)
Using a unique firm-provincial level panel dataset from 2005 to 2011, this study for the first time investigates the role played by corruption and provincial institutions in determining a company’s capital structure in Vietnam’s legal environment. Contrasting to the majority of previous studies, the results show that corruption has an insignificant influence on a company’s bank loans, consistent with institutional theory. However, the role of corruption is different for types of various capital structures after controlling for both unobservable characteristics and endogeneity problems. More specifically, corruption has significantly positive influence on short-term capital structure, but a negative impact on long-term loans. All of these results hold after a series of robust tests.